Exploring Visionary and Transformational Leadership among Islamic Leaders and Its Impact on Job Satisfaction in Indonesian Pesantren - Iwan Kurniawan; E. Syarifudin; Anis Zohriah (Sultan Publisher, 2024)
The background of this study includes the need for a deeper understanding of the factors that influence job satisfaction of operators in Salafiyah Islamic boarding schools in Banten Province, especially in the context of visionary and transformational leadership. This study explores the impact of visionary and transformational leadership on job satisfaction among operators at Salafiyah Islamic boarding schools in Banten Province. The research employs a quantitative method with a survey technique. One hundred sixty-six operators from Salafiyah Islamic boarding schools in Banten Province participated in the study. Data on visionary leadership, transformational leadership, and job satisfaction were collected using a Likert scale questionnaire with five response options. The questionnaire was validated before use. Data analysis was conducted using multiple regression analysis. The findings indicate that transformational leadership significantly affects job satisfaction, while visionary leadership does not. These findings highlight the importance of developing transformational leadership to enhance job satisfaction among operators of Salafiyah Islamic boarding schools, thereby improving their welfare and impacting the quality of Islamic boarding schools and other Islamic educational institutions. The implications of these findings underscore the importance of transformational leadership development as a strategy to improve the welfare and quality of management in the Islamic education environment, which can strengthen the position of pesantren as effective and competitive educational institutions.